The Effect of Consumer Loyalty on Purchasing Decisions for Khong Guan Biscuit Products - Saskia Prameswari; Morissan Morissan (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
Since its introduction in Indonesia in 1971, Khong Guan has maintained a dominant position in the Indonesian Fast Moving Consumer Goods (FMCG) industry, particularly in the assorted biscuit category, and holds a strong tradition of being served during Eid. This study aims to analyze the influence of consumer loyalty on purchasing decisions for Khong Guan Biscuits Red Segi products. The research background is based on the dominant position of the Khong Guan brand in the Indonesian Fast Moving Consumer Goods (FMCG) industry, especially in the assorted biscuit category and its tradition of being served during Eid, indicating strong and sustained consumer loyalty. This research operationalizes an explanatory quantitative design based on survey evidence from 226 consumers recruited from six Khong Guan Mart outlets and estimates the proposed model using multiple linear regression in SPSS. The analysis confirms that perceived quality, trust, satisfaction, brand image, price appraisal, and word-of-mouth communication serve as significant positive antecedents of purchasing decisions. In contrast, emotional connection emerges as a statistically significant negative determinant, highlighting the potential for maladaptive emotional engagement to attenuate consumers’ purchase propensity. Collectively, the seven predictors exhibit strong explanatory capacity, accounting for 89.3% of the observed variance in purchasing decisions. The research implications emphasize the importance of an integrated Integrated Marketing Communication (IMC) strategy to manage various dimensions of loyalty in order to encourage purchasing decisions and maintain long-term relationships with consumers in a competitive market.